Newton to Einstein the trail of light : an excursion to the wave-particle duality and the special theory of relativity - Baierlein, Ralph (Cambridge University Press, 1992)
This undergraduate text takes the reader along the trail of light from Newton's particles to Einstein's relativity. Like the best detective stories, it presents clues and encourages the reader to draw conclusions before the answers are revealed. The first seven chapters describe how light behaves, develop Newton's particle theory, introduce waves and an electromagnetic wave theory of light, discover the photon, and culminate in the wave-particle duality. The book then goes on to develop the special theory of relativity, showing how time dilation and length contraction are consequences of the two simple principles on which the theory is founded. An extensive chapter derives the equation E = mc2 clearly from first principles and then explores its consequences and the misconceptions surrounding it. That most famous of issues arising from special relativity - the aging of the twins - is treated simply but compellingly